THE EFFECT OF USING QUIZLET APPLICATION ON STUDENTS’ VOCABULARY MASTERY AT THE ELEVENTH GRADE OF SMA NEGERI 1 MATUR - Rahmawati, Riza; Roza, Veni; Reflinda; Melani, Melyann (STKIP Subang, 2026)
The purpose of this study was to determine the effectiveness of using Quizlet on the vocabulary mastery of eleventh-grade students at SMA Negeri 1 Matur. This study used a quantitative quasi-experimental method with two classes (XI F2 and XI F4) as samples. The data used in this study consisted of vocabulary mastery test results obtained from pre-test and post-test. The research results indicated that Quizlet was effective for students’ vocabulary mastery, with the mean score increasing from 58.71 to 87.64. The experimental class showed a significant improvement after the implementation of Quizlet in the learning process. Based on this increase in vocabulary mastery test scores (28.92) and the higher post-test results compared to the pre-test, Quizlet had a positive impact on students’ vocabulary mastery. The findings also showed that students became more active and engaged during the learning process. It can be concluded that Quizlet is an effective learning medium that enhances students’ activities, participation, and vocabulary mastery. The purpose of this study was to determine the effectiveness of using Quizlet on the vocabulary mastery of eleventh-grade students at SMA Negeri 1 Matur. This study used a quantitative quasi-experimental method with two classes (XI F2 and XI F4) as samples. The data used in this study consisted of vocabulary mastery test results obtained from pre-test and post-test. The research results indicated that Quizlet was effective for students’ vocabulary mastery, with the mean score increasing from 58.71 to 87.64. The experimental class showed a significant improvement after the implementation of Quizlet in the learning process. Based on this increase in vocabulary mastery test scores (28.92) and the higher post-test results compared to the pre-test, Quizlet had a positive impact on students’ vocabulary mastery. The findings also showed that students became more active and engaged during the learning process. It can be concluded that Quizlet is an effective learning medium that enhances students’ activities, participation, and vocabulary mastery.